2021
DOI: 10.5713/ajas.20.0521
|View full text |Cite
|
Sign up to set email alerts
|

The strategies for the supplementation of vitamins and trace minerals in pig production: surveying major producers in China

Abstract: Objective: Adequate vitamin and trace mineral intake for pig is important to achieve satisfactory growth performance. There are no data available on the vitamin and trace mineral intake across pig producers in China. The purpose of this study was to investigate and describe the amount of vitamin and trace minerals used in pig diets in China. Methods: A 1-year survey of supplemented vitamin and trace minerals in pig diets was organized in China. A total of 69 producers were invited for the survey, which represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The industry vitamin supplementation treatment levels were within ranges reported in commercial production surveys. 2,7 The reduced vitamin supplementation treatment contained vitamins A, D, E, and K added at NRC requirements 1 for gestation and water-soluble vitamins supplemented at approximately half the inclusion rate of the industry treatment. Gestating sows from three breeding groups within a batch farrow system were individually housed and received a common diet with industry standard vitamin levels prior to study enrolment.…”
Section: Animals Housing and Managementmentioning
confidence: 99%
“…The industry vitamin supplementation treatment levels were within ranges reported in commercial production surveys. 2,7 The reduced vitamin supplementation treatment contained vitamins A, D, E, and K added at NRC requirements 1 for gestation and water-soluble vitamins supplemented at approximately half the inclusion rate of the industry treatment. Gestating sows from three breeding groups within a batch farrow system were individually housed and received a common diet with industry standard vitamin levels prior to study enrolment.…”
Section: Animals Housing and Managementmentioning
confidence: 99%
“…In China, Yang et al [ 70 ] reported that the average ratios of dietary Zn concentrations relative to Chinese Feeding Standards [ 4 ] shown in Table 3 , ranged from 4.9 in Phase 1 nursery diets (8 to 15 kg body weight) to 1.0 in grower diets (25 to 60 kg body weight), and 1.4 to 1.6 in lactation and gestation diets ( Table 4 ). However, maximum Zn supplementation reported by some commercial swine operations in China ( Table 4 ) exceeded those reported in the U.S. survey for grower-finisher pigs (22 times the Chinese Feeding Standards recommendation) and sows (9 to 12 times the Chinese Feeding Standard recommendation).…”
Section: Zinc Feeding Practicesmentioning
confidence: 99%
“…Because the recommended maximum dietary Zn concentrations at various stages of production are greater for the current European Union guidelines compared with China and the United States ( Table 3 ), the estimated Zn consumption per market hog produced when using increased Zn supplementation levels for nursery pigs and gestating sows (Scenario 4 and 5) was comparable to that for the European Union (55,124 mg Zn/pig in Scenario 1) which does not allow comparable high Zn doses in these production phases. When comparing average dietary Zn supplementation from industry surveys in the United States [ 69 ], China [ 70 ], and Brazil [ 71 ] (Scenario 6 and 7) to increased Zn supplementation levels for nursery pigs and gestating sows in Scenario 4, the Zn consumed per pig marketed was 28% greater in the United States and 59% greater in Brazil but was 29% less in China. These results indicate that except for China, current average feeding levels of Zn in the United States and Brazil are unnecessarily high compared with the proposed optimal feeding scenario 4.…”
Section: Zinc Feeding Practicesmentioning
confidence: 99%
“…The requirement estimate for VD in growing pigs has not changed much over the years (from 1998 to 2012). In practice, the VD 3 supplementation is much higher than the NRC recommendation; the level of VD used in commercial swine diets varies widely (Yang et al, 2020). The design and outcome of published studies on the effects of feeding VD on the growth performance of pigs are displayed in Table 3.…”
Section: Efficacy and Dose Requirements Of Vitamin Dmentioning
confidence: 99%